(untitled) (Bangladesh Journal of Urology, 2022)
Introduction: For many years, the prone position has been the standard for PCNL, whereas the supine position has only recently gained popularity. The research on surgical outcomes is still lacking. Objective: To compare the surgical outcomes of prone versus supine PCNL. Methods: In this prospective study, 60 patients were enrolled who underwent for PCNL. Among them 30 patients had PCNL in prone position and 30 had PCNL in supine position. Patient’s body mass index (BMI), stone size, operative time, stone free rate, length of stay in hospital, and postoperative complications were all recorded. SPSS ver. 12.0 (SPSS Inc., Chicago, IL, USA) was used to analyze the data, which included Chi- Square and t-tests. A p-value of 0.05 or less was considered statistically significant. Results: There were no significant differences in gender, age, body mass index, stone location, or comorbidity between the two groups in this study. Operative time was significantly shorter in supine group (74.67 ± 11.94 min) than that of prone group (90.33 ± 8.70 min). Hospital stay was significantly longer in prone group (3.10 ± 0.61 min) than that of supine group (2.30 ± 0.47 min). Stone free rate was slightly higher in prone group than supine group but the difference was not statistically significant. Need of blood transfusion was little higher and post-operative complication was little higher in supine group but the differences was not statistically significant. Conclusion: Supine and prone PCNL are equally effective for achieving high stone free rate. However, supine position demonstrated shorter operative and hospital stay time compared to prone position. Bangladesh J. Urol. 2021; 24(2): 200-204